Processing of Norwegian complex verbs: Evidence for early decomposition. - Kush, Dave; Dillon, Brian; Eik, Ragnhild; Staub, Adrian (Memory & Cognition, 2019)
We examined the processing of Norwegian complex verbs—compounds consisting of a prepositional prefix and a verbal root—to investigate the lexical decomposition of such morphologically complex compounds. In an eyetracking-while-reading study, we tested whether reading time measures were significantly predicted by a compound verb's whole-word frequency, its root family frequency, or some combination thereof. The results suggest that whole-word and root family frequencies make independent contributions to first-fixation durations. Subsequent reading time measures were better predicted by either whole-word frequency, root family frequency, or both in tandem. We interpret these results as providing support for hybrid models of lexical representation, in which complex verbs are associated with an atomic (whole-word) representation linked to the lexical entries for the compound's constituent morphemes.